Meteorological data of Time Series Station Spiekeroog for 2017 - Badewien, Thomas Henry; Braun, Axel; Lübben, Andrea; Zielinski, Oliver (PANGAEA, 2025)
The Time Series Station Spiekeroog (TSS) was setup in 2002, in the tidal inlet between the East Frisian Islands of Langeoog and Spiekeroog in the Southern German Bight, at position 53°45′01.0″ N, 007°40′16.3″ E. The aim was to ensure the continuous measurement of physical, biological, chemical and meteorological parameters, even under extreme weather conditions such as storms, ice, and storm surges. The TSS was financed as part of the Deutsche Forschungsgemeinschaft (DFG) research unit BioGeoChemistry of Tidal Flats and the Ministry for Science and Culture of the Land of Lower Saxony (MWK). Here, air temperature, air pressure, relative humidity, wind speed and wind direction were measured in the year 2017. All raw data were revised and corrected for steps as range, outliers and stationarity checks. A detailed description of the Time Series Station Spiekeroog, its structure and instrumentation can be found in Zielinski et al. (2022) and in Reuter et al. (2009).
Keywords: climate records; extreme events; German Bight; Longterm measurements; meteorology; North Sea; Otzumer Balje; Research platform; Spiekeroog; Spiekeroog Coastal Observatory; Time Series Station; Wadden Sea